Determinants of phubbing behaviour among youth: a systematic literature review - Masliya Yahya; Farah Fazlinda Mohamad; Ramlee Mustapha; Sara Shakilla Mohd Salim; Melati Sumari (Penerbit Universiti Kebangsaan Malaysia, 2024)
With the rapid development of smartphones in the market, “phubbing” which is an act of ignoring others because of a deepened focus on such electronic devices rather than establishing conversations has become more pertinent. The phenomenon of phubbing among youth is a result of their desire for up-to-date information or news particularly during their studies. The present average daily smartphone usage ranges from two to ten hours among youth. Smartphones have enabled people to communicate with others from literally anywhere and anytime. However, there is growing concern that smartphones may reduce social connections rather than enhance them. This article examined the determinants of phubbing among youth and explains the determinants that link to phubbing. In this study, a systematic review was used as a research method. This article examined and compiled data from 15 research works databases namely Scopus and Google Scholar on the topic of how the impact of mobile phone addiction and depression among youth are related to phubbing. Based on the thematic analysis conducted, this review produced four themes namely: 1) smartphone addiction; 2) internet addiction; 3) fear of missing out (FOMO); and 4) Nomophobia. The findings explained that the average early identification of the consequences helps to improve the psychological well-being of the youth on how to improve relationships among others when having a conversation, being present and actively listening, being a model of healthier behaviour, and being understanding towards each other. The present findings suggest that phubbing is an important factor in modern communications that warrants further investigation.